Profiles of SUMO and ubiquitin conjugation in an Alzheimer's disease model - McMillan, Laura E.; Brown, Jon T.; Henley, Jeremy M.; Cimarosti, Helena (Neuroscience letters, 2011)
► Global levels of ubiquitinated proteins increased in the hippocampus of Tg2576 mice. ► No global changes in either SUMO-1 or SUMO-2/3 conjugation in any brain regions analysed. ► SUMO conjugating and deconjugating enzymes, UBC9 and SENP-1, unaltered in Tg2576 mice. ► Total levels of AMPA and kainate receptors were also unaffected in Tg2576 mice. ► Posttranslational modification by ubiquitin may play a role in Alzheimer's disease. Alzheimer's disease (AD) is a major cause of disability in the elderly. The formation of senile plaques and neurofibrillary tangles are the main hallmarks of the disorder, whereas synaptic loss best correlates to the progressive cognitive decline. Interestingly, some of the proteins involved in these pathophysiological processes have been reported to be subject to posttranslational modification by ubiquitin and/or the small ubiquitin-like modifier (SUMO). Here we investigated global changes in protein SUMOylation and ubiquitination in vivo in a model of AD. We used Tg2576 transgenic mice, which overexpress a mutated human amyloid precursor protein (APP) gene implicated in familial AD. As expected, APP protein levels were dramatically increased in the hippocampus, cortex and cerebellum of Tg2576 mice. A significant increase in the global level of ubiquitinated proteins was observed in the hippocampus of Tg2576 mice. Significant or close to significant changes in individual bands of SUMO-1 or SUMO-2/3 conjugation were apparent in all brain regions investigated, although global levels were unaltered between wild-type and transgenic mice. Levels of SUMO-specific conjugating and deconjugating enzymes, UBC9 and SENP-1 were also unaltered in any of the brain regions analysed. Surprisingly, given the well-documented loss of synaptic function, total levels of the excitatory AMPA and kainate receptors were unaffected in the Tg2576 mice. These results suggest that alterations in SUMO substrate conjugation may occur and that global posttranslational modifications by ubiquitin may play an important role in the mechanisms underlying AD.